Trustworthiness of travel information sources on Instagram and intentions to visit Gopeng Perak / Mazlina Mahdzar ... [et al.] - Mahdzar, Mazlina; Kamarulzaman, Nurul Dafiqah; Michael Remy, Deirdre Serena Sendi; Zainal, Zakina Izienty; Mohd Shawal, Nurul Syafiqqah; Osman, Nurul Faziera (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
This study is particularly interested in examining the trustworthiness of travel information sources on Instagram, a popular social media platform as one of the tourism distribution channels. Travel information and attractions of Gopeng, a town in Perak, Malaysia was chosen and examined through an Instagram account. A total of 152 questionnaire was completed by '@gopengtravelgram' instagram followers. Descriptive, independent sample T-test, and regression analysis are performed to examine the differences in trustworthiness on Instagram based on gender and age and the relationship between followers' intentions to visit Gopeng as a tourism destination. The findings revealed that Instagram followers had a positive perceived trustworthiness of travel information sources on Instagram. Furthermore, trust in the information shared by the Instagram account could inspire followers to plan a trip to Gopeng. The findings of this study may be used by destination marketers employing Instagram accounts to strategize the information sources that encourage visitors to have a visit intention. This study also suggests that other Instagram travel accounts or influencers include and highlight important sources in their posting to benefit the followers.